Developing Teacher Performance Through Evaluation of Leading Schools at State Junior High School 1 Seunagan, Nagan Raya Regency - Putra, Irwansyah; Akmaluddin, Akmaluddin; Syarfuni, Syarfuni (Dinasti Research, 2025)
The purpose of the study describes the driving school in managing human resources, managing learning in order to, utilizing digitalization, implementing mentoring activities and budget management to develop teacher performance at State Junior High School 1 Seunagan. The research method is qualitative descriptive. Informants consist of the principal, education staff and teachers. Data collection using interviews, observation and documentation and analysis is descriptive qualitative. The results of the study indicate that in managing human resources in order to develop teacher performance, various training activities are carried out to teachers, both through seminars, workshops, discussions in teacher work groups and conducting supervision. In managing learning, it is done by designing learning in accordance with the Operational Curriculum of the Education Unit, implementing a differentiated learning pattern and implementing the P5 program in various learning activities by teachers. In utilizing digitalization, it is done by utilizing the teacher competency development platform, Learning Platform, Platform as a school resource and utilizing digital media such as the Canva application as a facility for designing learning and in carrying out mentoring activities, it is done by holding various discussion activities through academic supervision by the principal, discussions with supervising teachers, as well as training and mentoring, such as workshops and seminars.